Photopoetry, 1845-2015 a critical history - Nott, Michael (New York, NY, USA Bloomsbury Visual Arts, a trademark of Bloomsbury Publishing Inc, 2022)
From amateur experiments in scrapbooks and stereographs to contemporary photobook collaborations between leading practitioners, poets and photographers have created an art form that continues to evolve and deserves critical exploration. 'Photopoetry 1845-2015, a Critical History' represents the first account of this challenging and diverse body of work. Nott traces the development of photopoetic collaboration from its roots in 19th-century illustrative practices to the present day. Focusing on work from the UK and US, he examines how and why poets and photographers collaborate, and explores the currents of exchange and engagement between poems and photographs on the page. The book not only considers canonical figures, but brings to light forgotten practitioners whose work questioned and shaped the relationship between word and image. 'Photopoetry 1845-2015, a Critical History' provides a new lens through which to explore poetry, photography, and the spaces between them.
1. ̀... with Photographic Illustrations': The Birth of British Photopoetry, 1845 -- 1875 -- 2. Ìllustratable with a Camera': The United States and Beyond, 1875 -- 1915 -- 3. From Illustration to Collaboration: Picturing the City, 1913 -- 1956 -- 4. Shaping Photopoetic Space: 1957 -- 1994 -- 5. Site Rhyme, 1992 -- 2015: Photopoetry and the Architectures of Memory
Revision of author's theses (Ph. D.--University of St. Andrews, Scotland, 2015)
Includes bibliographical references and index.
Keywords: Literature and photography; English poetry -- Illustrations; American poetry -- Illustrations; Photography, Artistic; Photography -- United States; Photography -- Great Britain; Photobooks